Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1177/01427237030232004
|View full text |Cite
|
Sign up to set email alerts
|

Adult Responses to Young Children's Communicative Gestures: Joint Achievement of Speech Acts

Abstract: During the period of transition between prelinguistic and linguistic communication (the second year of life) the communicative signals are mostly non-conventionalized and their semiotic power is relatively low. In this paper, communication sequences observed at 16 and 22 months are analysed in order to determine how the partner's joint communicative activity allows the sharing of intentions conveyed by gestural and/or vocal signals. The adult's responses to two types of gestures -holding out an object and poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
10
0
2
Order By: Relevance
“…In addition, in a more exploratory vein, we also looked at whether caregivers would respond with different types of speech acts depending on the characteristics of infants' points. For example, caregivers may interpret whole-hand points rather as invitations to act on something and index-finger points to elaborate or comment on something (see Marcos, 1991;Marcos, Ryckebusch, & Rabain-Jamin, 2003;Masur, 1982;Olson & Masur, 2011).…”
Section: Studymentioning
confidence: 99%
“…In addition, in a more exploratory vein, we also looked at whether caregivers would respond with different types of speech acts depending on the characteristics of infants' points. For example, caregivers may interpret whole-hand points rather as invitations to act on something and index-finger points to elaborate or comment on something (see Marcos, 1991;Marcos, Ryckebusch, & Rabain-Jamin, 2003;Masur, 1982;Olson & Masur, 2011).…”
Section: Studymentioning
confidence: 99%
“…In contrast to iconic gestures that evoke a referent without its presence, the function of pointing gestures is to draw attention to present referents. Basically, the semantic process requires the observer to “relate the gesture to the situation” ( Marcos et al, 2003 , p. 217). However, 12-month-olds also use pointing to refer to objects that are not visible but had been present in the past ( Bohn et al, 2015 ).…”
Section: Development Of Pointingmentioning
confidence: 99%
“…More specifically, we know that mothers respond to infants' gestures with labeling utterances that should facilitate language acquisition Marcos, 1991;Marcos, Ryckebusch, & Rabain-Jamin, 2003;Masur, 1982;Olson & Masur, 2011). For example, Olson and Masur (2011) found that mothers responded most often to infants' pointing at 13 months with labels of the referenced objects or with internal state words labeling perception (e.g., What do you see?).…”
mentioning
confidence: 99%